African-Brazilian Culture and Regional Identity in Bahia, Brazil - Ickes, Scott (Book collections on Project MUSE., 2013)
This book examines how in the middle of the twentieth century, Bahian elites began to recognize African-Bahian cultural practices as essential components of Bahian regional identity. Previously, public performances of traditionally African-Bahian practices such as capoeira, samba, and Candomble during carnival and other popular religious festivals had been repressed in favor of more European traditions.